2022
DOI: 10.1111/psyp.14155
|View full text |Cite
|
Sign up to set email alerts
|

Concealed identity information detection with pupillometry in rapid serial visual presentation

Abstract: The concealed information test (CIT) relies on bodily reactions to stimuli that are hidden in mind. However, people can use countermeasures, such as purposely focusing on irrelevant things, to confound the CIT. A new method designed to prevent countermeasures uses rapid serial visual presentation (RSVP) to present stimuli on the fringe of awareness. Previous studies that used RSVP in combination with electroencephalography (EEG) showed that participants exhibit a clear reaction to their real first name, even w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…In the early five time windows of 500-600 ms, 500-700 ms, 500-800 ms, 500-900 ms and 500-1000 ms, the average amplitudes of pupil dilation at 200 ms presentation rate was significantly higher than those at 100 ms presentation rate. The possible explanation was that, pupil dilation was induced by inhibition of the parasympathetic nervous system and Edinger-Westphal nucleus, and the inhibition was controlled by the LC-NE system [8,10,11]. At the early stage within 1000 ms, the activation intensity of the LC-NE system at 200 ms presentation rate might be greater than that at 100 ms presentation rate, thus the size of pupil dilation at 200 ms presentation rate was higher than that at 100 ms presentation rate.…”
Section: B Pupillometry Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…In the early five time windows of 500-600 ms, 500-700 ms, 500-800 ms, 500-900 ms and 500-1000 ms, the average amplitudes of pupil dilation at 200 ms presentation rate was significantly higher than those at 100 ms presentation rate. The possible explanation was that, pupil dilation was induced by inhibition of the parasympathetic nervous system and Edinger-Westphal nucleus, and the inhibition was controlled by the LC-NE system [8,10,11]. At the early stage within 1000 ms, the activation intensity of the LC-NE system at 200 ms presentation rate might be greater than that at 100 ms presentation rate, thus the size of pupil dilation at 200 ms presentation rate was higher than that at 100 ms presentation rate.…”
Section: B Pupillometry Analysismentioning
confidence: 99%
“…Previous studies demonstrated that pupil dilation was related to target recognition. When subjects focused on targets, the pupils dilated [8][9][10]. Pupil dilation is induced by the inhibition of the parasympathetic nervous system and Edinger-Westphal nucleus, and the locus coeruleus-norepinephrine system (LC-NE) controls these inhibitory processes, which dominates the regulation of attention [8,10,11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also focused on research that introduces more accurate countermeasure resistant paradigms or applies the instruction for guilty participants to look at every familiar and unfamiliar face in the same way [27,28,35,38]. The results of the countermeasure instruction studies point out that this task attenuated the initial orienting response to the familiar face but still concealed that recognition was detected by overt avoidance of the familiar face.…”
Section: Bovard Et Al [42] 2019mentioning
confidence: 99%